Dati preliminari sui copepodi calanoidi bento-planctonici del genere Pseudocyclops del lago di Faro (Sicilia nord-orientale). Preliminar data on bentho-planktonic calanoid copepod Pseudocyclops genus of the lake Faro (north-eastern Sicily). - Zagami, G., G. Costanzo, N. Crescenti & C. Brugnano (Biologia Marina Mediterranea, 2005)
Shallow-water bentho-planktonic calanoid copepods have been intensively studied in the Mediterranean Sea. To date, only two species of the genus Pseudocyclops have been recorded in the Mediterranean Sea, P. obtusatus Brady and Robertson, 1873 and P. umbraticus Giesbrecht, 1893. Recently, the bentho-planktonic calanoid copepod P. xiphophorus Wells, 1967, previously recorded only in coastal waters of Mozambique, has been found together with congenus species P. umbraticus and Pseudocyclops sp. in the brackish Lake Faro. P. xiphophorus and Pseudocyclops sp. were recorded into fouling attached to submerged mooring posts and ropes, while P. umbraticus mainly from bottom during day-light and from plankton at night. This interesting zoogeographic distribution suggests that the Mozambican and Mediterranean Pseudocyclops populations exhibit a complete Tethyan pattern, and that the P. xiphophorus specimens occuring in Lake Faro are a relict population that may have given rise to new species Pseudocyclops sp.